2002
DOI: 10.1093/jac/dkf046
|View full text |Cite
|
Sign up to set email alerts
|

Patient compliance with antibiotic treatment for respiratory tract infections

Abstract: Despite doctors' expectations, non-compliance is common in short-term antibiotic therapy of respiratory tract infections (RTIs). This phenomenon has profound practical implications. It leads to ineffective management, the deterioration of patients' health, hospital admissions, additional costs and the emergence of antibiotic-resistant microorganisms. This article reviews methods of measuring compliance with antibiotics in the outpatient-based management of RTIs and research results. Causes of non-compliance ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
1
26

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(150 citation statements)
references
References 34 publications
5
117
1
26
Order By: Relevance
“…42 However, resistance levels will be lower if all courses of antibiotics are completed due to high adherence rates. 43 In the present study, CHWs delivered a similar number of counseling messages compared with FBHWs. Studies in other areas, such as sex education, have established the role of peers in helping to set norms even when they are less expert on an issue.…”
Section: Discussionmentioning
confidence: 85%
“…42 However, resistance levels will be lower if all courses of antibiotics are completed due to high adherence rates. 43 In the present study, CHWs delivered a similar number of counseling messages compared with FBHWs. Studies in other areas, such as sex education, have established the role of peers in helping to set norms even when they are less expert on an issue.…”
Section: Discussionmentioning
confidence: 85%
“…Improvements in adherence to antibiotic treatment regimens are hard to measure, particularly for prescriptions in ambulatory care where intake is not supervised. 44 Moreover, comparative assessments of the effectiveness of public awareness campaigns are problematic as different countries use varying parameters for evaluations and for measuring antibiotic use e.g. Defined Daily Doses (DDD) or number of packages prescribed per 1,000 inhabitants/day.…”
Section: Responsible Use and Public Awarenessmentioning
confidence: 99%
“…Efforts to improve the wastewater epidemiology approach for antibiotics will need to address: (a) heterogeneity in the temporal distribution of prescriptions over time; (b) heterogeneity in the spatial distribution of prescriptions (across the UK) over time; (c) heterogeneity in in vivo and environmental stability of the antibiotic, including sewage pipes prior to reaching the WWTP inlet [46]; and (d) variability in compliance rate. It has been shown that the compliance rate for antibiotics can depend on the number of doses per day and age [47][48][49]. Further consideration should be given to (e) the sample size and sampling method.…”
Section: Pharmaceutical Occurrence In the Thames River Catchmentmentioning
confidence: 99%